Correlation Of Positive IgM or IgG RDT (Rapid Diagnostic Test) Results with CRP (C-Reactive Protein) Levels in Dengue Hemorrhagic Fever Patients - Yaumi Tasu’a Salsabila; Pancawati Ariami; Ida Bagus Rai Wiadnya; Thomas Tandi Manu (Poltekkes Kemenkes Mataram, 2023)
Background: Laboratory diagnosis of Dengue Hemorrhagic Fever includes the IgM & IgG RDT (Rapid Diagnostic Test) examination which differentiates primary and secondary dengue infection. The presence of inflammation in the body caused by the dengue virus needs to be examined for C-Reactive Protein. Methods: This research is an analytical observational study with a cross sectional approach. Thesample used is a plasma sample of a patient diagnosed with DHF with a positive IgM or IgG RDT result. Results: Positive IgM RDT results were 6 people (17%) and positive IgG were 30 people (83%). The results of a qualitative CRP study were 24 people (67%) with positive CRP levels. Semi-quantitative CRP average level for positive IgG was29.33. The results of the Spearman's Rank statistical test obtained a value of p = 0.003 <0.05 which showed a significant result. Conclusion:Clinically it shows that the more positive IgM or IgG RDT results obtained, the higher the CRP level which indicates the severity/inflammation that is formed in the body.